2013
DOI: 10.3923/pjbs.2013.844.851
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of Methanolic Extract of Hiptage bengalensis Leaves in Alloxan Induced Diabetic Models

Abstract: Diabetes mellitus is a metabolic disorder characterized by hyperglycemia and its occurrence is increasing fast in most of the countries. Herbal medicine derived from plant extracts have been utilized increasingly for the treatment of various disorders like diabetes mellitus. The present study was designed to evaluate the antidiabetic activity of Methanolic Extract of Hiptage bengalensis L. Kurz (MEHB) in alloxan induced diabetic rats and chick model. Alloxan (120 mg kg-1) was used to induce diabetes in rats an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 8 publications
4
11
0
Order By: Relevance
“…The in ovo diabetes‐induced chick embryo model was developed by following the method of previous studies (Yoshiyama et al ., 2005; Maheshwari et al ., 2013; Sivajothi & Dakappa, 2014). Briefly, on the 14th day of incubation, fertile eggs were divided into groups (I–VII) and transilluminated to mark the air space area of the embryonated eggs.…”
Section: Methodsmentioning
confidence: 99%
“…The in ovo diabetes‐induced chick embryo model was developed by following the method of previous studies (Yoshiyama et al ., 2005; Maheshwari et al ., 2013; Sivajothi & Dakappa, 2014). Briefly, on the 14th day of incubation, fertile eggs were divided into groups (I–VII) and transilluminated to mark the air space area of the embryonated eggs.…”
Section: Methodsmentioning
confidence: 99%
“…Bachir and Bellil [97] and Shyamapada and Manisha [98] reported plant containing phytochemicals could be used in preventive strategies to reduce the risk of most diseases including cancer (99Dharmalingam and Nazni 2013). Different kinds of plants have antioxidant substances capable of scavenging free superoxide radicals protecting biological systems against the harmful effects of oxidative processes on macromolecules [12,36]. Recent study has shown that some extracts intake cause improve in some biochemical parameters of oxidative stress and exhibited reduce the risk of some diseases [37,44].…”
Section: Chemical Analysis Of Coriander (C Sativum) Extractmentioning
confidence: 99%
“…Administration of some plants significantly diminished the hyperglycemia in mildly diabetic mice [44,90,98]. Other studies reported ten percent of plant extract produced a significant decrease in plasma glucose levels in normal and streptozotocin induced diabetic rats when administered by intraperitoneal injection or gastric tube [4,12,18]. Moreover,, the researchers conducted decades over last has shown plant and plant based therapies have a potential to control and treat diabetes and its complications [82,103].…”
Section: Chemical Analysis Of Coriander (C Sativum) Extractmentioning
confidence: 99%
See 2 more Smart Citations